Satmar hasidizminin tarihi, toplum yapısı ve görüşleri - Çağlar, Aybike (My University, 2025)
Satmar cemaati, 1928 yılında eskiden Macaristan günümüzde ise Romanya sınırlarında kalan Satu Mare’de Rebbe Yoel Teitelbaum (1887-1979) tarafından kurulmuş Hasidik bir gruptur. İkinci Dünya Savaşı sonrasında ise Amerika’ya taşınmak durumunda kalmıştır. Burada gelişmiş, yeni kurumlar kurmuş ve daha çok üye kazanarak büyümüştür. İsrail, Kanada, İngiltere gibi diğer ülkelerde de bulunan Satmar’ın merkezi Amerika’dadır. Cemaat üyeleri, geleneksel Yahudi yaşam tarzını hayatın her alanında tavizsiz şekilde uygulamalarıyla, diğer etnik ve dini gruplardan izole yaşamaya çalışmalarıyla, geleneksel giyim-kuşamlarıyla ve modern kültürü reddetmeleriyle bilinmektedir. Siyonizm’e ve İsrail Devleti’ne sert bir şekilde karşı çıkması, bu karşıtlığı dünya kamuoyuna duyurmaya çalışmasıyla dikkat çeken Satmar cemaati, günümüzde Amerika’nın en büyük Hasidik grubunu oluşturmaktadır. Bu çalışmada Satmar Hasidik cemaati, bağlı olduğu gelenek, tarihsel süreci, liderleri, bir cemaat olarak yapısı, Siyonizm karşıtlığı ve diğer Hasidik gruplarla farkları bağlamında incelenecektir.

The Satmar community is a Hasidic group founded in 1928 by Rebbe Yoel Teitelbaum (1887–1979) in Satu Mare, a city that was then part of Hungary and is now located within the borders of Romania. After the Second World War, the community was compelled to relocate to the United States. There, it expanded, established new institutions, and grew by attracting more members. Although Satmar is also present in countries such as Israel, Canada, and the United Kingdom, its center is in the United States. Community members are known for their uncompromising observance of traditional Jewish lifestyle in all aspects of life, their efforts to live in isolation from other ethnic and religious groups, their traditional clothing, and their rejection of modern culture. The Satmar community is especially notable for its strong opposition to Zionism and the State of Israel, and for its efforts to make this stance known to the international public. Today, Satmar is the largest Hasidic group in the United States. This study will examine the Satmar Hasidic community in terms of the tradition it is rooted in, its historical development, leadership, communal structure, opposition to Zionism, and its differences from other Hasidic groups.
History, social structure and views of satmar hasidism
Keywords: Anti-Siyonizm History of Religions; Anti-Zionism; Dinler tarihi; Haredilik; Haredism; Hasidism; Hasidizm; History of religions; Judaism; Moshe Teitelbaum; Orthodox Judaism; Ortodoks Yahudilik; Satmar; Yahudilik; Yoel Teitelbaum